Corporate Characteristics and Occupational Injuries by Industry - Sunyoung Park; Myung-Joong Kim (Elsevier, 2023)
Background: Recent research on occupational injuries in companies has faced difficulties in obtaining representative data, leading to studies relying on surveys or case studies. Moreover, it is difficult to find studies on how a company's industry characteristics affect occupational injuries. This study aims to address these limitations. Methods: We collected 11 years of disclosure data from 1,247 listed companies in the Korean stock market and combined it with their occupational injury histories collected by the Republic of Korea Occupational Safety and Health Agency (KOSHA) to build a dataset. We attempted to analyze a linear panel model by dividing the dataset into manufacturing, construction, and other industries. Results: The higher proportion of full-time employees and better job skills correlate with lower occupational injuries in other industries. The wage increase reduces occupational injuries in manufacturing and other industries, but the substitution effect produces the opposite outcome in construction. Also, foreign ownership and credit ratings increase effectively reduce occupational injuries mainly in the manufacturing industry. Conclusion: Our results suggest that in explaining the relationship between corporate characteristics and occupational injuries, it is necessary to consider the nature of the industry more closely, and in particular, employment and labor policies for preventing occupational injuries need to be selectively applied according to industry. In addition, to improve the limitations and increase the usability of the research results, further detailed studies are needed in the future.